Cultural Ethnoconcepts and Substantial Ethnocodes of Moldavians in the Interpretation of National Values Vector: Array - Babina, Yuliana (Journal of Danubian Studies and Research, 2020)
The purpose of this article is to find and approve the definition of key terms: cultural ethno concept and substantial code.The national carpet, as well as the ethnic ornament, is one of the main cultural ethnoconcepts and substantial ethnic codes of the Moldavian nation, as well as for a number of other nationalities of the Carpathian-Danubian region. Prior Work– the research is built in a logical manner on the basis of the analysis of many studies of foreign and modern Moldovan scientists, museum exhibitions and artifacts, the author’s own empirical observations in the course of creative and work activities. Approach– presents a collection of information, a combination of methods, both theoretical and practical, of cultural studies was used, including polls and questionnaires in the course of experimental work with artists and students, observation, synthesizing and systematizing, and comparative analysis of information. Results– We believe that these cultural ethnoconcepts, codes, ethnic constants are real structure-forming frameworks, configurations that crystallize certain adaptive and constantly evolving cultural models. Implications– each element of the cultural and historical heritage of the people has a powerful and immortal value content that determines the cultural picture of the world of a given ethnic community for future centuries. Traditional values and cultural ethnoconcepts of the peoples of the Carpathian-Danube zone perform the most important role of culture as a whole, a protective function, the role of a talisman and represent an inextricable link between generations and times with eternal high spiritual values.